Analisis Kinerja Alat Raosting Kopi Kapasitas 2kg Tipe Silinder Horizontal - putri liana, enno; Fiatno, Aris; Gusman, Deddy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Roasting is a process of frying coffee without oil using high temperatures which aims to speed up the process of frying coffee beans. The coffee roasting process aims to form the taste and aroma of the coffee beans. The coffee roasting equipment used in this study was a horizontal cylinder type coffee roaster with a capacity of 2 kg. This machine rotates with an electric dynamo. It has a cylindrical tube with a length of 27.5 cm and the heat comes from an LPG (Liquefied petroleum gas) stove. The purpose of this research is to test the performance of coffee roasting equipment. The data that needs to be measured from this coffee roasting tool is the need for electrical power used, roasting capacity and the change in color of the coffee when it is roasted. The electric power used is 12 volts 15 amperes. The results of the dark roast test at 200°c at 21 minutes. The maximum capacity of this horizontal cylinder type roasting machine is 2 kilograms